Evaluating the hip-flask defence using analytical data from ethanol and ethyl glucuronide. A comparison of two models - Höiseth, G.; Nilsson, G.H.; Lundberg, R.; Forsman, M.; Kronstrand, C.; Nyström, I.; Oscarsson, C.; Ericsson, E.; Cherma, M.D.; Ahlner, J.; Kugelberg, F.C.; Kronstrand, R. (Forensic science international, 2020)
•Both ethanol concentrations in blood and urine and ethyl glucuronide/ethyl sulphate concentrations in blood can be used to objectively assess the hip-flask defence.•Previous experimental data are from single dose studies only.•The same models can be used when two doses are ingested, but only when the second dose is sufficiently high. Claimed intake of alcohol after a traffic incident, called the hip-flask defence, can be objectively assessed by different methods. One of them is the use of two consecutive ethanol concentrations in urine and the ratio between ethanol concentrations in urine and blood. Another one is the concentrations of ethyl glucuronide (EtG) and ethyl sulphate (EtS) in blood and their ratio to ethanol. The experimental basis for both these models is from single dose studies only. The aim of this study was therefore to describe the kinetics of ethanol, EtG and EtS after ingestion of two repeated doses of ethanol and to investigate the usefulness of the different models for the assessment of the hip-flask defence. Thirty-five subjects ingested a first dose of 0.51 g of ethanol per kilo body weight, and two hours later a second dose (the hip-flask drink) of 0.25, 0.51 or 0.85 g of ethanol per kilo body weight. Ten urine and 17 blood samples were collected and analysed for ethanol, EtG and EtS using fully validated methods. It was investigated if all subjects fulfilled the criteria for recent drinking, according to the two different models, when using the samples collected 180–240 minutes after start of first dose drinking. According to the first model, increase in urinary ethanol concentrations and a ratio UAC/BAC below 1.3 indicated recent drinking. According to the second model, increase in blood EtG concentrations and a ratio ethanol (g/kg)/EtG (mg/L) above 1 indicated recent drinking. All subjects in the high dose group fulfilled all criteria for recent drinking. One subject in the medium dose group and nine subjects in the low dose group failed to show increasing UAC and/or a UAC/BAC ratio below 1.3. One subject in the low dose group failed to show increasing concentrations of blood EtG, but all subjects showed a ratio ethanol/EtG above 1. The present study showed, by the use of experimental data, that both two models used to investigate the hip-flask defence can be used, but only when the hip-flask dose is sufficiently high.